Patients' perception of the duration of analgesia provided by intrathecal bupivacaine/morphine after laparoscopic colorectal surgery: a prospective cohort study - Joost L. C. Lokin; Claudia Savelkoul; Ramon R. J. P. van Eekeren; Mark V. Koning (Anesthesiology and Perioperative Science, 2024)
Abstract Purpose The addition of intrathecal morphine to general anesthesia for laparoscopic colorectal surgery is an effective method of providing analgesia. However, the analgesia duration of approximately 24 hours poses the risk of rebound pain on the second postoperative day. Therefore, this study aimed to investigate the patients' perception on postoperative pain management using the International Pain Outcomes questionnaire on both the first and second postoperative day. Methods This prospective single-center cohort study was conducted between November 2020 and March 2021 and included forty patients. The primary outcome was a difference in postoperative pain on the first and second postoperative day. Secondary outcomes included opioid consumption, interference of pain with activities, side effects, and patients’ perception and satisfaction with pain treatment. Results The intensity of postoperative pain did not increase on the second postoperative day NRS [numeric rating scale] 5 (2–7 [0–10]) vs 5 (3–7 [1–10]), p=0.414), but the percentage of time spent in severe pain increased (20% (10-40 [0-90]) vs 30% (20-50 [0-80]), p=0.010). There was no difference in opioid consumption (6 mg (0–12) [0–42] vs 6 mg (0–12) [0–29], p=0.914). Pruritis (NRS 2 (0–6 [0–10]) vs 0 (0–3 [0–8]), p=0.001) and dizziness (NRS 2 (0–7 [0–10]) vs 0 (0–2 [0–9]), p=0.002) decreased on the second postoperative day. Patients reported high satisfaction during the first two days after surgery (NRS 8 (7–9) [0–10] vs 8 (7–9) [0–10], p=0.395). Conclusion Intrathecal morphine is a suitable analgesic modality in laparoscopic colorectal surgery within an enhanced recovery after surgery program, without causing important rebound pain. Pain scores, however, may be further reduced by adding non-opioid analgesics.